Japanese ODA and private sector development in the Philippines and Thailand a comparative analysis - Phelan, Bernadette E. (1995)
After a long spell of support for the Keynesian approach of demand management by the public sector, official development assistance (ODA) has recently been used to promote greater participation in development through increased access of long-term funds by the private sector on projects highly supportive of building up local initiative. In this paper, the experiences of Thailand and the Philippines in the use of Japanese ODA are reviewed. In particular, the implementation of the two-step loan program (or formally called Financial Intermediary Loan Program) of the Overseas Economic Cooperation Fund (OECF) of Japan in the two countries is compared. The two-step loan program is intended to funnel long-term credits to small entrepreneurs, such as small-and medium-scale export-oriented businesses, including small farmers and agricultural cooperatives. The primary purpose of this study is to present the role of ODA in the development of the private sector and hence, partially explain the distinct differences in the two countries' economic performance. The paper also uses unpublished official data which were obtained from the interviews conducted.
Keywords: Japanese economic assistance; Philippines -- Literary collections -- 1970-1993; Thailand -- Literary collections -- 1970-1993